Long Run Financial Market Cointegration and its Effect on International Portfolio Diversification - Chakrabarty, Anindya; Ghosh, Bidyut Kumar (Indian Journal of Finance, 2011)
This paper empirically investigates the causality and long run equilibrium relationship between the Indian stock market and the stock market indices of two developed countries namely USA and UK using Engle Granger causality and Cointegration regression tests. The study depicts that USA and UK market factors influence Indian stock market in the long run. Financial integration is the key to delivering competitiveness, efficiency and growth. But will integration also bring about financial stability? One of the main motivations behind these cross border investments is portfolio hedging, which unfortunately is not effective in an environment of high cross border financial cointegration. It is evident from the present study that investment in US and UK market by an Indian investor with an intention of reducing risk will bear no fruit in the long run. While the increasing surge of international trade and cross border investment in an era of globalization and multinational companies (MNCs), is buttressing financial integration across countries, the financial stability is still a far cry.